Local Control, Resources and the Nova Scotia Steel and Coal Company - Inwood, Kris (Historical Papers / Communications historiques, 1986)
AbstractFinancial market activity indicates that Maritime interests lost control of the Nova Scotia Steel and Coal Company in 1915 and 1916. Production and financial records of the firm suggest that poor profitability contributed to the change of ownership. The firm's weakness is traced to its resource base and the resulting high costs of production. The causation implicit in conventional accounts is reversed: control and ownership changes were a result of, rather than a cause of, production difficulties and weak profitability.